ANALISIS KETERAMPILAN GURU DALAM MENGELOLA KELAS RENDAH PADA PEMBELAJARAN BAHASA INDONESIA SDN 08 KP. JAWA I KOTA PARIAMAN - Lindri Martinopa; Nur Azmi Alwi; Diren Agasi; Yulia Maulani (Program Studi PGSD FKIP Universitas Bung Hatta, 2022)
This study aims to analyze the skills of teachers in managing low grades in Indonesian subjects at SDN 08 Kp. Jawa I city of Pariaman. This research is a qualitative research with descriptive qualitative type of percentage. The subjects in this study were 6 low grade teachers at SDN 08 Kp. Jawa I. The object of this research is the skills of classroom teachers in low class management in Indonesian language subjects. Data collection techniques in this study used observation techniques, interview techniques, and documentation techniques. The data analysis method used in this research is descriptive percentage analysis method. From the results of the overall study regarding the skills of teachers in managing low grades in Indonesian subjects at SDN 08 Kp. Jawa I City of Pariaman is categorized as very good, although there are some aspects that are still good or not good. Low grade teacher at SDN 08 Kp. Jawa I Kota Pariaman is very professional in managing classes and can overcome unfavorable classes and maintain them.